The concept of Algerian identity according to the perspective of the historical colonial school - ouldboussiafa, Rchid (Journal of Social Sciences and Humanities, 2023)
The study focuses on The colonial historical school perception of Algerian identity, the starting points and motives for studying all the Algerian identity-related religion, language, history, traditions and customs, and how all such knowledge has been used to entrench the foundations of colonialism in Algeria. The first idea promoted by this school is that Algeria was not a nation and that it does not have the basic elements to be a homeland, and this idea continues to be echoed in some French political and academic circles to date.